Literary Languages Between Choice and Imagination - Peti-Stantić, Anita (2009)
The author presents the idea that the language policy is ultimately grounded in linguistic culture, that is, the set of behaviours, assumptions, cultural forms, prejudices, folk belief systems, attitudes, stereotypes and ways of thinking about language, as well as the religious-historical circumstances associated with that particular language. For that reason, the history of literary language formation, especially the recent history, has to be taken into respect. The Croatian example is especially illuminating because it clearly shows that a language community based on communication may follow its own path, while the literary language community based on a traditional linguistic culture may go a different way, but also that the literary langauge community is based on a linguistic culture and traditions which are at the same time imagined and historically justified. Since this was not recognised by those who represented overt language policy after the break-up of Yugoslavia, many changes that were proposed missed the point and were not accepted.
Projekt MZOS
ENG